Pump–probe laser system at the FXE and SPB/SFX instruments of the European X‐ray Free‐Electron Laser Facility. (15th February 2019) - Palmer, Guido; Kellert, Martin; Wang, Jinxiong; Emons, Moritz; Wegner, Ulrike; Kane, Daniel; Pallas, Florent; Jezynski, Tomasz; Venkatesan, Sandhya; Rompotis, Dimitrios; Brambrink, Erik; Monoszlai, Balazs; et al.
Abstract : The ultrafast pump–probe laser at the SASE1 undulator beamline of the European XFEL is described. Abstract : User operation at the European X‐ray Free‐Electron Laser Facility started at the SASE1 undulator beamline in fall 2017. The majority of the experiments utilize optical lasers (mostly ultrafast) for pump–probe‐type measurements in combination with X‐ray pulses. This manuscript describes the purpose‐developed pump–probe laser system as installed at SASE1, implemented features and plans for further upgrades.